2018
DOI: 10.3390/life8030035
|View full text |Cite
|
Sign up to set email alerts
|

Green Rust: The Simple Organizing ‘Seed’ of All Life?

Abstract: Korenaga and coworkers presented evidence to suggest that the Earth’s mantle was dry and water filled the ocean to twice its present volume 4.3 billion years ago. Carbon dioxide was constantly exhaled during the mafic to ultramafic volcanic activity associated with magmatic plumes that produced the thick, dense, and relatively stable oceanic crust. In that setting, two distinct and major types of sub-marine hydrothermal vents were active: ~400 °C acidic springs, whose effluents bore vast quantities of iron int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
147
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(151 citation statements)
references
References 286 publications
(478 reference statements)
3
147
0
1
Order By: Relevance
“…Accordingly, we could readily synthesize membranes of highly oxygen sensitive iron(II, III) hydroxides by co‐precipitation of Fe 2+ and Fe 3+ along the solution interface of our microfluidic device. This is significant for origin of life chemistry since green rust (among other iron oxyhydroxides) is proposed to have existed in alkaline hydrothermal vents on the early Earth, forming inorganic membranes transected by pH and other gradients, and may have been capable of driving prebiotic redox and phosphorus chemistry . In this experiment, the alkaline solution contained 0.5 m NaOH, whereas the acidic iron solution contained 0.33 m Fe 2+ and 0.17 m Fe 3+ .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Accordingly, we could readily synthesize membranes of highly oxygen sensitive iron(II, III) hydroxides by co‐precipitation of Fe 2+ and Fe 3+ along the solution interface of our microfluidic device. This is significant for origin of life chemistry since green rust (among other iron oxyhydroxides) is proposed to have existed in alkaline hydrothermal vents on the early Earth, forming inorganic membranes transected by pH and other gradients, and may have been capable of driving prebiotic redox and phosphorus chemistry . In this experiment, the alkaline solution contained 0.5 m NaOH, whereas the acidic iron solution contained 0.33 m Fe 2+ and 0.17 m Fe 3+ .…”
Section: Resultsmentioning
confidence: 96%
“…Steep disequilibria across mineral membranes are thought to be significant for the emergence of metabolism in an alkaline vent setting, and since disequilibria‐converting engines linked to ATP/ADP or PP i hydrolysis are essential for life, it has been suggested that analogous processes–though mineral‐driven–may have been involved in the emergence of metabolism . Particularly the mineral green rust, a mixed valence iron oxyhydroxide, has been proposed to serve various prebiotic functions as an engine, electron transfer agent, and catalyst for organic synthesis . A major challenge for origins‐of‐life studies, particularly in such complex geochemical systems as vents, is the vastness of the search space that involves both physical and chemical factors such as temperature gradients, catalytic materials, porosities, and concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that protocellular life at hydrothermal vents must have come equipped with proteins, RNA and cell membranes, which in turn makes amino acids, nucleotides and vesicles minimal prerequisites for hydrothermal vent origin of life scenarios. However, at present, photochemically driven cyanosulfidic and cyanosulfitic protometabolism is the only path to forming all of these prerequisites in one environment, and this protometabolism proceeds only at surfaces exposed to sunlight.An alternative point of view is that both the prebiotic chemistry and subsequent evolution occurred in underwater alkaline hydrothermal vents [7,11,12]. Recently, this hypothesis has gained support from the detection of nanomolar concentrations of amino acids of possible abiotic origin, found in the oceanic lithosphere proximal to underwater hydrothermal environments [13].…”
mentioning
confidence: 99%
“…An alternative point of view is that both the prebiotic chemistry and subsequent evolution occurred in underwater alkaline hydrothermal vents [7,11,12]. Recently, this hypothesis has gained support from the detection of nanomolar concentrations of amino acids of possible abiotic origin, found in the oceanic lithosphere proximal to underwater hydrothermal environments [13].…”
mentioning
confidence: 99%
“…It was suggested that redox reactions between precipitated transition metal sulfides, such as iron monosulfide (FeS), could have provided the free energy and electrons for prebiotic synthesis through the generation of pyrite (Wächtershäuser 1988). Another approach also involving FeS and ferrous-ferric oxyhydroxide, but in the form of a putative membrane separating alkaline sulfide-bearing hydrothermal fluids from acidulous Fe-bearing ocean, had the effect of imposing both a redox and a pH gradient with a total potential approaching 1 V, sufficient theoretically to drive the reduction of carbon dioxide (Russell andHall 1997, 2006). These gradients are, and were, sustainable for at least 100,000 years (Ludwig et al 2011).…”
Section: Hydrothermal Systems and Electron And Proton Availabilitymentioning
confidence: 99%